Pemetaan Lokasi Gabungan Kelompok Tani Pada Dinas Pertanian Provinsi Gorontalo - Sulis Rahayu Ahmad (Universitas PGRI Semarang, 2018)
Combined Farmer Group (Gapoktan) is a combination of several farmer groups that partner and jointly doing business in the field of agribusiness to achieve income and increase production of farming for members and other farmers. The Provincial Agricultural Office of Gorontalo has the duty to carry out the formulation, implementation of policies, monitoring and evaluation in the field of agricultural extension. One of the counseling is done at the Combined Farmer Group in Gorontalo province.This research aims to facilitate the search of Gapoktan location which will be given assistance and agricultural extension in Gorontalo Province region and designing mapping of location of gapoktan based on android At Gorontalo Provincial Agricultural Service In order to search location and time used more effective and efficient and easier for people to get information related with more detailed gapoktan. Based on whitebox testing obtained the appropriate results and applications can run well in some types of android phones Keywords: Geographic Information System, Location, Gapoktan, Android